RESEARCH TREND OF WORKING CAPITAL MANAGEMENT - Rahmawati, Sisca Dian; Lamidi; Zakiyah, Nadiya Fikriyatus; Murningsih, Setia; Putra, Febrianur Ibnu Fitroh Sukono (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
Given the importance of working capital in firm dynamics, the main objective of this research is to highlight the main gaps and insights in the working capital literature and suggest future research, as well as to know the development trend of working capital management research published by leading journals. For this reason, a bibliometric analysis was carried out using bibliographic information from Scopus for the topic "working capital management." The method used in this quantitative research uses Bibliometric analysis. A quantitative analytic approach was used to analyze published studies from 1992 to 2022. The mapping software used was VOS Viewer and biblioshiny R to analyze the data obtained and visualize research trend data. The results of the analysis show that the development of articles with the theme of Working Capital Management continues to increase from year to year, although not constant and essential. The most published authors of articles on Working Capital Management are Karri, T. and Michalski, G. The United Kingdom is the country most cited. 2019 was the year with the highest number of publications on Working Capital Management. The International Journal of Recent Technology and Engineering is the highest source that occurs in 2019. Business, Management and Accounting are the most mentioned trending topics with a total of 38%.